KEBERADAAN OLAHRAGA BILLIARD DALAM MASYARAKAT DI KECAMATAN MANDAU KABUPATEN BENGKALIS - Maruzuki, Jami; Bahri, Syamsul (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Billiard is one type of ball game that can build a self-image and can lift the dignity of the nation in foreign countries. At first this billiard sport is only a means to achieve physical and spritural health and can build a good character personality. Currently the development of billiard sports in the country has developed quite rapidly. With many match event, billiard sports have the same opportunities as other sports where billiards are also played in SEA GAMES, ASIAN GAMES, and world-class games, proved the many enthusiasts of this sport. The purpose of this study was to find out whether the billiard sports conducted by the community in accordance with the permits issued by the Mandau district government. In addition, to find out the causes that affect so that this billiard sport is misused by people in the district of Mandau. This study used qualitative research methods. The study consisted of five informants selected by using purposive sampling technique. This study uses data collection techniques such as in-depth interviews, observation, and documentation. The results of this study are the standards and licensi of this sport is not eligible. So it can be concluded that in Mandau sub-district there is still a billiard palce that has not been licensed so far i expected to the authorities in the subdistrict Mandau to be more assertive again in a comprehensive effort related to the exercise permit licensi in order to run in accordance with its function as a place for the means of exercise and able to reduce actions that disturb the people lived around the place billiard.Keywords: community, billiard, licensing.